Effects of Analgesic Advertisements on Community in Hegarmanah Village, Jatinangor - Nurhayati binti Shaharuddin; Eva M. Hidayat; Jupiter Sibarani (Faculty of Medicine Universitas Padjadjaran, 2014)
Background: Currently, there are numerous analgesic advertisements which have been published in various media and have also attracted attention of the society. The aim of this study is to find out effects of analgesic advertisements on awareness and attention towards these advertisements on the community in Hegarmanah Village, Jatinangor.Methods: The study used the descriptive method with participants consisting of community members in Hegarmanah Village who have seen, watched or heard about the analgesic advertisements and who were aged 18 years and above. The sample for this study consisted of 100 respondents. This study was conducted in September 2012–December 2012.Results: The results showed that 82% of the respondents have seen the ads in at least the last 3 months and mostly watched them on television. About 52% of respondents agreed that many of the ads did not provide sufficient information. In addition, 50% only read a little bit of the ads rather than the whole advertisement. Fifty three percents of the respondents had the intention to try the medication after seeing the ads. More than 80% were aware about how to use the medication, medication’s side effects, warnings and contraindications and 65% agreed that, they could make a better decision on their health condition after seeing the ads.Conclusions: The analgesic advertisements indeed affected the community by making them aware about the ads and attracted them to buy as well as try the product itself. Further studies on factors which influence intake of over-the-counter analgesic drugs and also about the self-medication are required. [AMJ.2014;1(2):1–6]Keywords: Analgesic advertisements, effects, society Pengaruh Iklan Analgesik terhadap Masyarakat di Desa Hegarmanah, JatinangorLatar Belakang: Saat ini, banyak iklan analgesik yang ditayangkan di beberapa media dan telah menarik perhatian masyarakat. Penelitian ini bertujuan untuk mengetahui pengaruh iklan analgesik terhadap kesadaran dan pemahaman mengenai obat analgesik pada masyarakat di Desa Hegarmanah, Jatinangor.Metode: Penelitian ini menggunakan metode deskriptif dengan melibatkan partisipan yang terdiri dari anggota masyarakat di Desa Hegarmanah yang telah melihat, menyaksikan atau mendengar tentang iklan analgesik dan berusia 18 tahun ke atas. Sampel penelitian ini terdiri dari 100 responden. Penelitian ini dilakukan pada bulan September 2012-Desember 2012.Hasil: Hasil penelitian menunjukkan bahwa 82% dari responden telah melihat iklan di setidaknya 3 bulan terakhir dan sebagian besar menonton di televisi. Sekitar 52% dari responden setuju bahwa banyak dari iklan tidak memberikan informasi yang cukup. Selain itu, 50% hanya membaca sedikit iklan daripada seluruh iklan. Lima puluh tiga persen dari responden memiliki niat untuk mencoba obat setelah melihat iklan. Lebih dari 80% yang sadar tentang penggunakan, efek samping, peringatan dan kontraindikasi obat dan 65% setuju bahwa, mereka bisa membuat keputusan yang lebih baik tentang kondisi kesehatan mereka setelah melihat iklan.Simpulan: Iklan analgesik memang memengaruhi masyarakat dengan membuat mereka paham tentang obat yang diiklankan dan menarik mereka untuk membeli serta mencoba produk tersebut. Penelitian lebih lanjut tentang faktor-faktor yang memengaruhi penggunaan obat analgesik yang dijual bebas dan juga tentang pengobatan sendiri masih diperlukan. Kata kunci: iklan analgesik, efek, masyarakat DOI: 10.15850/amj.v1n2.346